2016
DOI: 10.1007/s00540-016-2183-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute pain trajectories and the persistence of post-surgical pain: a longitudinal study after total hip arthroplasty

Abstract: This study showed that during the postoperative period patients differed in terms of pain intensity profiles and that these differences were associated with outcomes for up to 6 weeks following surgery. Pain trajectories were not predictive of persistent postoperative pain status at 6 months. Nonetheless, these results highlight the importance of patient heterogeneity in acute postoperative pain and pain-related outcomes months after THA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
63
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 43 publications
6
63
2
Order By: Relevance
“…Results from the acute pain trajectory model are strikingly similar to those obtained among patients undergoing total hip arthroplasty (Page et al., ), namely highlighting subgroups of patients with unchanging elevated or mild pain intensities as well as those with rapidly improving pain intensity. The literature is controversial regarding the association between acute post‐operative pain trajectories and CPSP outcomes (Althaus, Arranz Becker, & Neugebauer, ; Bonnet, Lavand'homme, France, Reding, & De Kock, ; Page et al., ).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Results from the acute pain trajectory model are strikingly similar to those obtained among patients undergoing total hip arthroplasty (Page et al., ), namely highlighting subgroups of patients with unchanging elevated or mild pain intensities as well as those with rapidly improving pain intensity. The literature is controversial regarding the association between acute post‐operative pain trajectories and CPSP outcomes (Althaus, Arranz Becker, & Neugebauer, ; Bonnet, Lavand'homme, France, Reding, & De Kock, ; Page et al., ).…”
Section: Discussionsupporting
confidence: 69%
“…Results from the acute pain trajectory model are strikingly similar to those obtained among patients undergoing total hip arthroplasty (Page et al., ), namely highlighting subgroups of patients with unchanging elevated or mild pain intensities as well as those with rapidly improving pain intensity. The literature is controversial regarding the association between acute post‐operative pain trajectories and CPSP outcomes (Althaus, Arranz Becker, & Neugebauer, ; Bonnet, Lavand'homme, France, Reding, & De Kock, ; Page et al., ). While acute post‐surgical pain, typically measured as a static variable, is a common risk factor for CPSP (Katz, ; Katz & Seltzer, ; Katz et al., ; Perkins & Kehlet, ; Schug & Bruce, ), the lack of such significant association in pain trajectory studies highlights the importance of examining the heterogeneity of pain responses acutely in the understanding and the prevention of CPSP.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…ese probabilistic latent class models can capture the progressive change of pain over time [10] that is unique to specific subgroups of individuals. In adults after total hip arthroplasty, Pagé et al (2016) identified 4 pain trajectories in the acute postoperative period [11]. Importantly, preoperative variables such as pain and anxiety predicted pain trajectory membership.…”
Section: Introductionmentioning
confidence: 99%
“…Among the three (mild, moderate and severe pain) clusters, patients with a severe pain trajectory turned out to have a high risk of chronic pain 6 months after the surgery. A similar approach has been attempted following total hip arthroplasty, by evaluating a GBTM-based acute pain trajectory for 5 days after the surgery, although it failed to predict future chronic pain [18]. It seems that information on pain intensity for approximately 7 days after surgery has substantially contributed to the accuracy of prediction of the likelihood of development of chronic postsurgical pain.…”
mentioning
confidence: 99%